P03.10 Analyzing the role of reoperation in high grade gliomas: a retrospective study. (6th September 2019) - González, V; Ibáñez, J; Fuster, J; Brell, M
Abstract: BACKGROUND: Primary treatment of high grade glioma consists in a standard therapeutic regimen that involves maximal surgical safe resection followed by chemoradiotherapy. Unfortunately, due to its aggressive behavior, relapse is the rule in all patients. When this situation arises, treatment strategy is less clear and reintervention in selected cases is controversial and still a reason for debate. MATERIAL AND METHODS: We retrospectively analysed (n=393) patients affected with high grade glioma in our institution during a period of 14 years (from January 2005 to March 2019). Treatment modality at diagnosis and recurrence, overall and progression-free survival were reviewed. RESULTS: There were 320 grade IV and 73 grade III gliomas. Regarding to the modality of treatment, more procedures with radical intention (n=227) than biopsies (n=166) were performed. At progression, glioblastoma patients were treated in (n=118) cases. We decided to reoperate (n=30) cases who also received second-line chemotherapies.The other group (n=88) received only systemic treatment. Median overall survival assessed from initial diagnosis was 23 months(95% CI 17–28.9) versus 17 months (95% CI 15.7–18.2) in patients with surgery at recurrence comparing to those who did not undergo second surgery, (p< 0.05). In addition, clinical condition of most patients did not worsen after the second surgery. CONCLUSION: Second surgery for recurrent glioblastoma was associated with a survival advantage. Reoperation should be considered in patients with tumours located in low eloquence areas and good clinical condition.